Lung Ultrasound to Detect Pneumothorax in Children Evaluated for Acute Chest Pain in the Emergency Department: An Observational Pilot Study - Scialanga, Barbara; Buonsenso, Danilo; Scateni, Simona; Valentini, Piero; Schingo, Paolo Maria Salvatore; Boccuzzi, Elena; Mesturino, Maria Alessia; Ferro, Valentina; Chiaretti, Antonio; Villani, Alberto; Supino, Maria Chiara; Musolino, Anna Maria (Frontiers in Pediatrics, 2022)
Background Spontaneous pneumothorax is a relatively uncommon and poorly studied condition in children. While several protocols have been developed to evaluate the use of lung ultrasound for dyspneic adult patients in the emergency department, no specific guidelines are present for pediatric emergency physicians. Objectives We prospectively analyzed children with acute chest pain and clinical suspicion of pneumothorax evaluated at the pediatric emergency department. Methods We consecutively enrolled children aged 5–17 years presenting to the pediatric emergency department with clinically suspected pneumothorax based on sudden onset of acute chest pain. After clinical examination, all children underwent lung ultrasound followed by chest X-ray (reference standard). We enrolled 77 children, of which 13 (16.9%) received a final diagnosis of pneumothorax. Results The lung point had a sensitivity of 92.3% (95% CI 77.8–100) and a specificity of 100% (95% CI 94.4–100) for the detection of pneumothorax. The “barcode sign” had a sensitivity of 100% (95% CI 75.3–100) and a specificity of 100% (95% CI 94.4–100) for the detection of pneumothorax. Conclusion Lung ultrasound is highly accurate in detecting or excluding pneumothorax in children with acute chest pain evaluated in the pediatric emergency department. If pneumothorax is suspected, but the lung point is not visible, the barcode sign should always be sought as it could be a form of massive pneumothorax.